Average photon energy assessment based on modelled spectra from the National Solar Radiation Database for Lima, Peru - Sevillano-Bendezú, M.A.; Conde, L.; de la Casa, J.; Töfflinger, J.A. (IOP Publishing, 2022)
The photovoltaic performance under operating outdoor conditions is affected by the variability of the solar spectrum. The spectral distribution is quantifiable using the average photon energy ( APE ). In the present study, we characterize the spectral distribution in a low-latitude location such as Lima - Peru through a decade of simulated solar spectra obtained on demand from the National Solar Radiation Database and taking as a reference one year of ground-based experimental data following the decade of theoretical spectra. This characterization utilizes annual and monthly averages of irradiance-weighted APE s. The results indicate a difference of only 0.2% between the average annual APE for the decade and the annual ground-based experimental APE . Additionally, the theoretical monthly APE s for the decade show a seasonality consistent with our experimental data for the summer months but not for the winter months.
Keywords: Irradiance; Latitude; Environmental science; Seasonality; Spectral line; Spectral power distribution; Atmospheric sciences; Solar irradiance; Radiation; Photovoltaic system; Meteorology; Geography; Physics; Statistics; Mathematics; Geodesy; Engineering; Optics; https://purl.org/pe-repo/ocde/ford#1.05.04